Duck and (re)cover : - Little, Steven S. (John Wiley & Sons, 2009)
Duck and (re)Cover is the ultimate business owner's guide to prevailing and prospering through tough economic times. It questions much of the "conventional wisdom" we all hear about recessions and instead offers an irreverently common-sense approach to survival and growth in the midst of economic uncertainty. This book focuses on the most significant challenges and opportunities facing embattled businesses today